2019
DOI: 10.1111/corg.12302
|View full text |Cite
|
Sign up to set email alerts
|

Changing words: How temporal consistency in a CEO's use of language toward shareholders and stakeholders affects CEO dismissal

Abstract: Research Question/Issue The present study examines how temporal consistency in the CEO's use of language in public documents affects the board's decision to dismiss the CEO. Research Findings/Insights Using CEOs' letters to shareholders from 304 large firms in the United States in 1998–2007, we found that CEO dismissal risk is lower when the CEO consistently uses language that signals conformity to a prevailing institutional logic: shareholder‐value orientation. In contrast, dismissal risk is greater when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 121 publications
0
10
0
Order By: Relevance
“…Cikaliuk, Eraković, Jackson, Noonan, & Watson, 2019) to define and pursue the purpose of their companies (Harrison et al, 2019). The stakeholder perspective on the role of the board chair in determining and pursuing the organizational purpose could also aid in understanding the role of ownership in such interactions and the importance of adopting a long‐term perspective and one that takes into account the legitimate interests of a broader set of stakeholders beyond shareholders (Shin & You, 2020).…”
Section: Agenda For Future Research On the Role Of The Board Chairmentioning
confidence: 99%
“…Cikaliuk, Eraković, Jackson, Noonan, & Watson, 2019) to define and pursue the purpose of their companies (Harrison et al, 2019). The stakeholder perspective on the role of the board chair in determining and pursuing the organizational purpose could also aid in understanding the role of ownership in such interactions and the importance of adopting a long‐term perspective and one that takes into account the legitimate interests of a broader set of stakeholders beyond shareholders (Shin & You, 2020).…”
Section: Agenda For Future Research On the Role Of The Board Chairmentioning
confidence: 99%
“…They also reveal that future‐oriented disclosures are more common among outsider, younger, and inexperienced CEOs. Scholars have also shown that consistency in the CEO's shareholder‐value language during his or her tenure increases the credibility of the CEO's signals and is positively perceived by the board, thereby reducing the odds of dismissal (Shin & You, 2020). In addition, Green et al (2019) find that a signal of extraversion in executive speech leads to longer tenure and lower turnover due to the corresponding signal of talent and leadership.…”
Section: Five Key Research Themesmentioning
confidence: 99%
“…The individual CEO can frame the narrative that they want to convey to the readership (Dikolli et al, 2020;Mmako, 2016). The chosen narrative could have effects on the readers/shareholders, e.g., consistently using words in the letter that emphasise shareholder value, year after year, has been found to markedly reduce the chances of the CEO being dismissed (Shin & You, 2020). Asay et al (2018a) find that use of personal pronouns and the presence of a picture of the CEO with the shareholder letter both affect investors' perceptions.…”
Section: Ceo Shareholder Letters As Vehicles For Impression Managementmentioning
confidence: 99%